Histopathological Changes of Experimental Hydatidosis in Liver and Spleen of Albino Mice: Age and Sex Effect - Al-Kuraishi, Azhar H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: A number of investigators have carried out experimental infections of hydatidosis, using albino mice as an experimental animal model, but there was disagreement on the effect of strain, sex and age of this model. Materials and Methods: Two hundred and forty mice (120 males and 120 females) were injected intraperitoneally with a single dose of 2000 protoscolices (PSCs) /mouse at four ages (3-4, 7-8, 10 and 20 weeks). Each age group consisted of 60 mice (30 males and 30 females); in which 15 animals of each sex were the treated group, while the other 15 animals were a control group (injected with normal saline). Five animals from each age and sex were sacrificed at one, two and four month po stinjection, and their livers and spleens were collected for histopathological examination. Results: the highest numbers of cysts and the most severe histopathological changes in livers and spleens of mice were observed at the age 3-4 weeks in both sexes. These changes increased with time post-infection. The changes became more severe in males than females in the age 7-8 weeks, but at the age 20 weeks, the females showed the most severe histopathological changes, while the age 10 weeks showed the lowest changes in both sexes. Conclusion: The age and the sex of the host can modify the course of infection with hydatidosis, and the present results suggest that, mice at the ages 3-4 (in both sexes) and 7-8 weeks old (males) produce the most severe pathological changes in these organs. The more resistant age to hydatidosis was observed at 10 weeks old in both sexes.